KEPENTINGAN EKONOMI POLITIK SINGAPURA DALAM MENERAPKAN SISTEM EKONOMI ISLAM (2007-2014) - Nur Hilda Mardiah; Yuli Fachri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This paper is a study of the phenomenon of international economy and politics in the study of international relations which elaborates and analyzes the political and economic interest of Singapore to implement Islamic economic system. Broad trading network owned by Singapore resulted in instability of Singapore’s capitalist economy during crisis. This underlies the application of the Islamic economic system as an alternative economic system to keep the economy stable.This paper was developed based on the framework of liberalism perspective supported by national interest theory as well as the use level analysis of the state as the main actor in international relations. This study uses qualitative research methods to the study of literature as a source of information.Application of Islamic economic system in Singapore other than as an alternative economic system is also an economic and political interests of Singapore to the Middle East demanding their economic system based on Islam in trade agreements. Strategic steps in applyintg Islamic economic system is an effort to maximize Singapore's bilateral relations with the Middle East.Kata kunci : Islamic economic system, economic crisis, interest, Middle East.